Evaluation of Induction Training: A Survey of Low and Mid-level Managers at Nepalese Development Banks - Sthapit, Arhan (Administration and Management Review, 2012)
Induction training is important to apprise the new entrants about the organisation and to orientate and socialise them with its philosophy, goals, work culture, procedures, systems, compensation (salary, leaves, facilities, etc.) and expected employee-behaviours. The article is based on the author’s recent survey (November-December, 2011) as to how managers evaluate the induction training of their respective organisations in terms of Kirkpatrick’s (1983, 2004) four-level/criteria training evaluation model (Reaction, Learning, Behaviour and Results). Surveying a sample of low and middle-level managers of Nepalese development banks established after F/Y 2005/06, the study found that the induction training as effective in terms of ‘learning,’ and ineffectual on the ‘Behaviour-change’ criterion. The findings of the study should prove instrumental in providing important inputs to human resource managers, policy-makers and HRD-professionals. Administration and Management Review Vol. 24, No. 1, January, 2012, Page 29-44